2021
DOI: 10.14366/usg.20170
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided ethanol ablation for cystic thyroid nodules: effectiveness of small amounts of ethanol in a single session

Abstract: To evaluate the efficacy of ethanol ablation (EA) in the treatment of cystic thyroid nodules using low dose ethanol regardless of initial volume of the nodule or aspirates. Methods: 61 nodules in 60 patients were treated with EA from October 2013 to January 2020. In each patient, EA was performed only once using less than 5mL ethanol (99.5%) instilled and removed completely after a few minutes of retention. Nodule volume, symptom score, cosmetic score and complications were evaluated before and after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Second, the results of this study [ 1 ] showed that volume reductions after EA were much lower in predominantly cystic nodules than in cystic lesions (65.1% vs. 90.1%). However, in previous studies, EA achieved somewhat higher volume reduction rates for predominantly cystic nodules (74.9%-82.4%) [ 3 ].…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Second, the results of this study [ 1 ] showed that volume reductions after EA were much lower in predominantly cystic nodules than in cystic lesions (65.1% vs. 90.1%). However, in previous studies, EA achieved somewhat higher volume reduction rates for predominantly cystic nodules (74.9%-82.4%) [ 3 ].…”
mentioning
confidence: 86%
“…We read with great interest the article published by Cho et al entitled "Ultrasound-guided ethanol ablation for cystic thyroid nodules: effectiveness of small amounts of ethanol in a single session" [ 1 ]. In this article, the authors evaluated whether low-dose (less than 5 mL) ethanol injections were effective for treating cystic and predominantly cystic thyroid nodules.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We greatly appreciate your detailed and constructive comments. In our study, we defined a "low dose" as less than 5 mL [ 1 ]. However, we did not propose a precise amount of ethanol according to the nodule volume or the cystic nature of the thyroid nodule.…”
mentioning
confidence: 99%